LOKALISASI ORE - Ratnasari, Lucia (MATEMATIKA, 2006)
﻿﻿Let be a noncommutative ring and be a multiplicative subset of . The right (left) ring of quotients does not exist for every. A necessary condition of existence right (left) ring of quotients is right (left) permutable and right (left) reversible. A multiplication subset is called a right (left) denominator if it is right (left) permutable and right (left) reversible. The ring has a right (left) ring of quotients with respect to if and only if is a right (left) denominator set. We can construct right (left) ring of quotients by using Ore localizations.